Building consumer loyalty through green marketing: an Egyptian perspective - Amr Samir Aly; Luna Santos-Roldán; Beatriz Palacios-Florencio (Environmental Research Communications)
Despite extensive global research on the relationship between green marketing practices and consumer loyalty, limited attention has been given to how these dynamics unfold in developing countries such as Egypt. This study addresses this gap by expanding the brand loyalty model to include Environmental Concern (EC), Green Marketing Communications (GMC), and Green Product Packaging (GPP) as key antecedents influencing consumer Brand Loyalty (BL), with a particular focus on the mediating role of Brand Trust (BT). Conducted in the Egyptian context, this quantitative study surveyed 460 randomly selected respondents using a structured questionnaire, with data analyzed through the AMOS program. The findings reveal that EC, GMC, and GPP have significant and positive direct effects on BL. Furthermore, BT plays a critical mediating role, strengthening the relationship between these green marketing variables and consumer loyalty. Grounded in the Theory of Planned Behavior (TPB), this study emphasizes the role of environmental attitudes, which correlate with environmental concern, in influencing trust in green brands. This trust subsequently contributes to brand loyalty. By connecting green marketing practices with both attitudinal and behavioral intentions, the research offers a theoretical basis for comprehending the factors that enhance consumer loyalty within the realm of green marketing. From a practical standpoint, the results highlight the significance of honest and transparent green marketing communications, sustainable packaging, and trust-building strategies, including third-party certifications and green supply chain practices. Companies should proactively educate consumers about their environmental initiatives through awareness campaigns, social media, and transparent reporting to foster environmental concern and loyalty. Furthermore, organizations need to keep abreast of sustainability trends and technologies to enhance their practices and meet consumer expectations, thereby ensuring long-term trust and loyalty.